EU competence and investor migration - Sarmiento, D; van den Brink, M (Cambridge University Press, 2023)
In this chapter, we examine the issue of competence to confer residence and citizenship based on a donation or investment in the light of international and European law as they stand today. We show that the national competence to do this is part of the sovereign nature of the modern state, which implies the ability to create a people and delimit the scope of the population granted a right to settle in the national territory, underpinned by rules behind such delimitation. We also explain why investment migration per se cannot be presented as unlawful and outlines the avenues for the eventual disciplining of its offshoots in areas unrelated to migration as such, thus connecting particularly well with Peter Spiro’s analysis of relevant international law.